Diagnostic utility of VEGF mRNA and SP1 mRNA expression in bronchial cells of patients with lung cancer. Issue 4 (24th March 2014) - Cha, Na; Lv, Ming; Zhao, Yu‐Jie; Yang, Di; Wang, En‐Hua; Wu, Guang‐Ping
Abstract Background and objective Bronchial brushing is important for cytological diagnosis of lung carcinoma; however, cytological evaluation alone remains relatively insensitive. The aim of this study was to assess the diagnostic utility of vascular endothelial growth factor (VEGF) messenger ribonucleic acid (mRNA) and specificity protein 1 (SP1) mRNA in bronchial brushings in patients with or without lung cancer. Methods VEGF mRNA and SP1 mRNA were measured in liquid‐based cells from bronchial brushings in patients with verified lung cancer (n = 93) and with benign lung disease that included tuberculosis (n = 51). This was done using the reverse‐transcription polymerase chain reaction. Results Both VEGF mRNA and SP1 mRNA were significantly more likely to be expressed in the cancer group than in the control (benign) group, whatever their cell type. It was also more often found in the tuberculosis group than in the inflammation group (P < 0.01). In the cancer group, VEGF mRNA was significantly correlated with SP1 mRNA (P < 0.01). Of the 36 false negative cytology results, 30 gave positive results for VEGF mRNA and 34 for SP1 mRNA. The four false positive VEGF results were all diagnosed as tuberculosis. VEGF mRNA gave the highest diagnostic performance with serial use: sensitivity 89.2% and accuracy 90.3%. This was significantly better than cytology (P < 0.01). Conclusions Detection of VEGF mRNA and SP1 mRNA in bronchial brushing cells may be used as an ancillary tool to cytological diagnosis for detection of early‐stage lung cancer. It may also help distinguish tuberculosis from other causes of lung inflammation.